Penyediaan Bahan Ajar Digital Akuntansi Pada SMK Kartini Batam - Serly Serly; Herlina Natalia (ConCEPt - Conference on Community Engagement Project, 2021)
The pandemic that took place in 2020 has affected many activities in various fields, including in the field of education. Indonesian students must undergo distanced learning to minimize the spread of the virus in the school environment. Therefore, the role of educational technology is very important in supporting the process of distanced learning. To support the learning process of class XI computerized accounting subject, the authors carry out the preparation of digital teaching materials containing computerized accounting lessons in accordance with the 16 basic competencies in the school syllabus. The method of implementation will be started with data collection which is done by interviewing teachers of related subjects to obtain information for the design of the output. The preparation of digital teaching materials uses the Myob Accounting program version 25, Microsoft Powerpoint, OBS Studio, and Filmora. The results of the activity are 16 powerpoints containing explanations and ways of inputting trade transactions on the MYOB application and 16 video tutorials on how to input trade transactions in the MYOB application. Recommendations for the next PkM related to the preparation of outputs are to be able to obtain more information about the teaching system from teachers of related subjects to compile outputs that are in accordance with the habits of the teacher's delivery of material.